2014
DOI: 10.5114/wiitm.2014.41636
|View full text |Cite
|
Sign up to set email alerts
|

Videoscopic adrenalectomy - when does retroperitoneal seem better?

Abstract: IntroductionVideoscopic adrenalectomy is the gold standard for the surgical treatment of benign adrenal tumours. The two most common approaches are the lateral transperitoneal approach (LTA) and the posterior retroperitoneal approach (PRA). So far it has not been established which is the preferable one. The choice depends primarily on the surgeon's preference and contraindications for a particular approach in individual cases.AimTo compare the two most common approaches for videoscopic adrenalectomy, LTA and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…It is due to the broader knowledge of the anatomy of the peritoneal cavity, skills gained in other laparoscopic procedures, as well as a larger operative field. However, according to numerous reports, PRA is easier to perform and is associated with less pain in the postoperative period [16,22,25]. The above observations are confirmed by our median operative time for PRA, 91.8 ± 30.8 min and its downward tendency.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is due to the broader knowledge of the anatomy of the peritoneal cavity, skills gained in other laparoscopic procedures, as well as a larger operative field. However, according to numerous reports, PRA is easier to perform and is associated with less pain in the postoperative period [16,22,25]. The above observations are confirmed by our median operative time for PRA, 91.8 ± 30.8 min and its downward tendency.…”
Section: Discussionsupporting
confidence: 76%
“…Opponents of the method indicate gas embolism and the release of catecholamines as possible risks of the increase in the CO 2 pressure [21]. However, this has not been confirmed in practice [16,22].…”
Section: Discussionmentioning
confidence: 99%
“…The number of non-severe complications of laparoscopic adrenalectomy, reaching 10%, is acceptable. Conversions to the open method are done in 5% of all cases [13][14][15]. Similar results were found in the presented study as well as in patients with malignancies and in patients with benign tumours not hormonally active.…”
Section: Rycina 2 Nowotwór Nadnerczy -Rezonans Magnetycznysupporting
confidence: 75%
“…There are authors who prefer retroperitoneal access in the case of smaller tumors. 25 Recent meta-analyses showed no statistical differences between laparoscopic and retroperitoneoscopic access regarding perioperative outcomes; however, postoperative recovery was slightly faster in the latter. 24,26 For instance, Zon ca et al suggested that retroperitoneoscopic access can also be used safely in morbidly obese patients, and indeed might be associated with more favorable postoperative course, shorter hospital stay, better cosmetic outcome and quicker recovery.…”
Section: Discussionmentioning
confidence: 98%
“…No doubt minimally invasive surgery is preferred in the treatment of most tumors. There are authors who prefer retroperitoneal access in the case of smaller tumors . Recent meta‐analyses showed no statistical differences between laparoscopic and retroperitoneoscopic access regarding perioperative outcomes; however, postoperative recovery was slightly faster in the latter .…”
Section: Discussionmentioning
confidence: 99%